Laminated Ti3SiC2/Zr based composites obtained by spark plasma sintering; Journal of Physics: Conference Series; Vol. 1989 : Prospects of Fundamental Sciences Development (PFSD 2021) - Sedanova E. P. Elizaveta Pavlovna; Murashkina T. L. Tatiana Leonidovna; Krotkevich D. Dmitry; Mingazova Yu. R. Yuliya Rafailovna; Lider A. M. Andrey Markovich; Travitsky (Travitzky) N. Nakhum (2021, 2021)
Title screen